The effectivity of ear plug utilization on emergence delirium incidence in pediatric patient undergoing general inhalated anesthesia - Perdana, Aries; Kapuangan, Christopher; Zahra, Raihanita (Bali Journal of Anesthesiology, 2019)
Background. Emergence Delirium (ED) also known as emergence agitation, is a postoperative condition characterized by aberrant cognitive and psychomotor behaviors such as agitation, irritable, uncompromising, uncooperative, inconsolably crying following general anesthesia. The incidence of ED in pediatric patients in Dr. Cipto Mangunkusumo hospital was 39,7%. During emergence state, auditory stimulation induces thalamic synapse in lateral amygdala which leads to over response of fear (one of the risk factor of ED). A high noise level in operating room can be reduced with ear plug application to the patient. Design and Method. A double blind randomized clinical trial towards 1-5 years old pediatrics who underwent inhalation general anesthesia in Dr. Cipto Mangunkusumo hospital from September-December 2018. One hundred and seven subjects were randomized after a consecutive sampling into two groups. Earplug group (n=53) with application of ear plug at the end of surgery, while in control group (n=54) without application of ear plug. The incidence of ED and time to extubation were recorded. ED was measured using Pediatric Anesthesia Emergence Delirium (PAED) scale. All the data was analyzed using multivariate logistic regression and ANCOVA. Result. Incidence of ED in ear plug group was 16.7% while in control group was 32.1% (OR = 0.402; CI 95% 0.152-1.062; p=0.066). Mean value of time to extubation in ear plug vs control group (5.76+3.23 minutes) vs (6.54+ 3.67 minutes) with mean difference of 0.825(0.530-2.180); p=0.230. Conclusion. Ear plug application at the end of anesthesia was not statistically effective. However, it was clinically effective in reducing the incidence of ED in pediatric patient underwent inhalation anesthesia.